Attitudes toward professionalism education in Otolaryngology–Head and Neck Surgery residency programs. (10th July 2014) - Nichols, Brent G.; Stadler, Michael E.; Poetker, David M.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Resident professionalism development is important for physician training and patient care. Meaningful professionalism curriculum requires collaboration between learners and educators. We aimed to better understand attitudes of Otolaryngology–Head and Neck Surgery (OHNS) program directors (PDs) and residents toward professionalism education. Study Design Prospective survey. Methods We identified contemporary methods of professionalism evaluation and education and formulated questions to assess attitudes toward professionalism education. Surveys were electronically distributed to 104 PDs who were asked to forward a separate survey to residents. Results The resident survey was completed by 110 OHNS residents, and the PD survey was completed by 33 OHNS PDs. The majority of residents (78%) and faculty (84%) believed professionalism could be taught. Role modeling (93%) and morbidity and mortality conference (90%) were the most common methods of education. Faculty questionnaires (100%) and nursing/ancillary staff questionnaires (93%) were the most common methods of resident evaluation. The majority of residents considered faculty mentoring (66%) and small group discussions (56%) to be useful methods for teaching professionalism, whereas only 14% considered formal lectures useful. Residents valued questionnaires by faculty (98%), medical staff (97%), and patients (94%) for professionalism evaluation. Conclusion We are the first to study OHNS residents and PDs attitudes toward professionalism evaluation and education. Residents value mentoring programs and small group sessions rather than formal didactics and value evaluation from multiple sources. Programs should consider incorporating these specific educational and evaluative methods into their professionalism curricula. Level of Evidence N/A. Laryngoscope, 125:348–353, 2015